Dampak Iklan terhadap Kelas Sosial dalam Masyarakat - Aryo Bimo (Humaniora, 2011)
Article described the growth of advertisement in Indonesia that is quite rapid and its’ impacts on the social classes. Advertisement’s rapid growth was evidenced by the relatively high increase in expenditure, i.e. up to 13 percent. If calculated to October 2009, the total advertising expenditure Indonesia had reached 40 trillion IDR. Advertising was often considered as a cause of increased consumptive lifestyles in society. In addition, advertising was considered to be responsible in creating social classes in society. Therefore, article would like to discuss how these ads can distinguish groups of people with communication conducted in an advertisement.